(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This study investigated the factors influencing organisation of intramural sports programme in public secondary schools in Ekiti Central Senatorial District, Ekiti State. It also identified the factors of organization of intramural sports programme. The research adopted descriptive survey design. The population of the study was 615. Six hundred and fifteen respondents were tested. Multistage sampling procedure was used to select 615 respondents. Researcher’s designed questionnaire was the instrument for data collection. The instrument was validated by three Lecturers in the Department of Human Kinetics Education and tested for reliability using Pearson’s Product Moment Correlation and a coefficient of 0.76 was obtained. Five null hypotheses were tested using inferential statistics of Chi-squire (X²) at 0.05 alpha level. The results of the study revealed that: Proper planning, organizational patterns, professional competence, of managers, fund budgeted has significant influence on and organizing intramural sports programme in public secondary school in in Ekiti Central Senatorial District of Ekiti State cal.-value 416.18> crit.-value 16.92 at 9; cal.-value 465.26> crit.-value 16.92 at 9 df ; cal.-value 502.36> crit.-value 16.92 at 9 df ; cal.-value 452.21> crit.-value 16.92 at 9 df and; cal.-value 0.320> crit.-value 487.75 at 9 df at 0.05 alpha level. This study concluded that Planning, Sports facilities, Organizational patterns, sports expert and funds has significant influence the organization of intramural sports programme in public secondary schools in Ekiti Central Senatorial District. It was recommended that Adequate planning should be put in place by the sports managers and physical education teachers in organizing intramural sport programe in public secondary schools in Ekiti central senatorial district, Sports managers in public secondary school should follow good organization pattern of planning intramural sport programme in secondary schools in Ekiti central senatorial district .There should be adequate provision of sport facilities in public secondary schools to ensured effective intramural sport programmes, Available sport experts should be put in charge of planning and organization of intramural sport programme and encouraged so that they can be motivated to put in their best effort,Enough funds should be made available so as to be able to organize an effective intramural sort programme.